A study of the immiscible co2 wag performance after gas flooding under various controlling parameters - Tareq Ahmed Ali Mashrah, 1988-, author 635226; Azman Ikhsan, supervisor 285387; Fakulti Kejuruteraan Petroleum dan Kejuruteraan Tenaga Diperbaharui 558316 (2014)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2014